Marketing adjustments to production modernization: the case of the Nicaraguan rice industry - Austín, James E. (Managua (Nicaragua), 1972)
Sumario (En)
Tesis (Doc Bus)
Keywords: ARROZ; MERCADEO; PRODUCCION; NICARAGUA; ASPECTOS ECONOMICOS